2000
DOI: 10.1016/s1097-2765(00)80430-x
|View full text |Cite
|
Sign up to set email alerts
|

The ISWI Chromatin-Remodeling Protein Is Required for Gene Expression and the Maintenance of Higher Order Chromatin Structure In Vivo

Abstract: Drosophila ISWI, a highly conserved member of the SWI2/SNF2 family of ATPases, is the catalytic subunit of three chromatin-remodeling complexes: NURF, CHRAC, and ACF. To clarify the biological functions of ISWI, we generated and characterized null and dominant-negative ISWI mutations. We found that ISWI mutations affect both cell viability and gene expression during Drosophila development. ISWI mutations also cause striking alterations in the structure of the male X chromosome. The ISWI protein does not coloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
374
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(390 citation statements)
references
References 58 publications
13
374
1
2
Order By: Relevance
“…Since the functions of chromatin remodelers confer epigenetic effects that lead to stable changes in gene expression, short-term exposure to dsRNA in the ovary or in the embryo may lead to long-lasting RNAi-induced phenotype. Mutations in other members of the chromatin remodeler gene group are known to have gametogenic and/or embryonic effects in fruit flies (Daubresse et al, 1999;Deuring et al, 2000;Kehle et al, 1998;McDaniel et al, 2008); it remains to be seen if these genes would also serve as efficacious pRNAi targets for pest insect control. The ability of western corn rootworm to develop resistance to crop protection chemistries (Gray et al, 2009;Narva et al, 2013) and transgenic insect resistance traits based on Bt proteins (Gassmann et al, 2011) creates the need for new approaches to corn rootworm control to combine with existing technology.…”
Section: Discussionmentioning
confidence: 99%
“…Since the functions of chromatin remodelers confer epigenetic effects that lead to stable changes in gene expression, short-term exposure to dsRNA in the ovary or in the embryo may lead to long-lasting RNAi-induced phenotype. Mutations in other members of the chromatin remodeler gene group are known to have gametogenic and/or embryonic effects in fruit flies (Daubresse et al, 1999;Deuring et al, 2000;Kehle et al, 1998;McDaniel et al, 2008); it remains to be seen if these genes would also serve as efficacious pRNAi targets for pest insect control. The ability of western corn rootworm to develop resistance to crop protection chemistries (Gray et al, 2009;Narva et al, 2013) and transgenic insect resistance traits based on Bt proteins (Gassmann et al, 2011) creates the need for new approaches to corn rootworm control to combine with existing technology.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, chromatin remodeling ATPases are known to have roles in both oogenesis and development. The Drosophila chromatin remodeling ATPases that are essential for oogenesis include Iswi (Deuring et al, 2000), Chd1 (McDaniel et al, 2008), Mi-2 (Kehle et al, 1998), and possibly Brm (He et al, 2014). In addition to oviposition defects, it was reported that the lack of maternal iswi leads to developmental arrest in an early stage of oogenesis (Deuring et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Currently ISWI complexes have been found in a variety of organisms from yeast to humans Ito et al, 1997;Varga-Weisz et al, 1997). In Drosophila, localization of ISWI protein on polytene chromosomes shows a lack of colocalization with the bulk of RNA polymerase II, suggesting that ISWI complexes are involved in processes other than transcription (Deuring et al, 2000;reviewed in Dirscherl and Krebs, 2004).…”
Section: Iswi-related Chromatin Remodeling Complexesmentioning
confidence: 99%